Using isotopic dilution to assess chemical extraction of labile Ni, Cu, Zn, Cd and Pb in soils - Garforth, Judith M.; Bailey, Elizabeth H.; Tye, Andrew M.; Young, Scott D.; Lofts, Stephen (Elsevier, 2016)
Chemical extractants used to measure labile soil metal must ideally select for and solubilise the labile fraction, with minimal solubilisation of non-labile metal. We assessed four extractants (0.43 M HNO3, 0.43 M CH3COOH, 0.05 M Na2H2EDTA and 1 M CaCl2) against these requirements. For soils contaminated by contrasting sources, we compared isotopically exchangeable Ni, Cu, Zn, Cd and Pb (EValue, mg kg-1), with the concentrations of metal solubilised by the chemical extractants (MExt, mg kg-1). Crucially, we also determined isotopically exchangeable metal in the soil–extractant systems (EExt, mg kg-1). Thus ‘EExt - EValue’ quantifies the concentration of mobilised non-labile metal, while ‘EExt - MExt’ represents adsorbed labile metal in the presence of the extractant. Extraction with CaCl2 consistently underestimated EValue for Ni, Cu, Zn and Pb, while providing a reasonable estimate of EValue for Cd. In contrast, extraction with HNO3 both consistently mobilised non-labile metal and overestimated the EValue. Extraction with CH3COOH appeared to provide a good estimate of EValue for Cd; however, this was the net outcome of incomplete solubilisation of labile metal, and concurrent mobilisation of non-labile metal by the extractant (MExt < EExt > EValue). The Na2H2EDTA extractant mobilised some non-labile metal in three of the four soils, but consistently solubilised the entire labile fraction for all soil-metal combinations (MExt ≈ EExt). Comparison of EValue, MExt and EExt provides a rigorous means of assessing the underlying action of soil chemical extraction methods and could be used to refine long-standing soil extraction methodologies.